Clinical characteristics and outcomes in 50 children with autoimmune hepatitis: a retrospective study from a single centre in China - Yang, Yandi; Yang, Fan; Yang, Min; Liu, Zherui; Liu, Shuhong; Lian, Linlin; Chang, Binxia; Shen, Lijun; Tian, Hua; Liang, Qingsheng; Chen, Songhai; Dong, Shuna; et al. (Frontiers in Medicine, 2026)
ObjectivesLittle is known about autoimmune hepatitis (AIH) in Chinese children. The study aimed to explore the clinical characteristics and predictors of outcomes in the Chinese paediatric AIH cohort.MethodsA retrospective review of all paediatric AIH cases from 2015 to 2025 was conducted at a single centre in Beijing, China.ResultsOf the 50 enrolled cases, 39 (78.0%) presented with type 1 AIH (consisting of 30 female children (60.0%); median age of 9.2 years). At presentation, 24 (48.0%) patients had cirrhosis, 11 (22.0%) had liver failure, and 10 (20.0%) had decompensated cirrhosis at presentation. Compared to type 1, children with type 2 were younger and had higher levels of serum alanine aminotransferase [270.0 (166.0, 599.0) U/L vs. 610.0 (510.0, 1231.0) U/L, p = 0.003] and aspartate aminotransferase [335.0 (172.0, 756.0) U/L vs. 576.0 (433.0, 1020.0) U/L, p = 0.013]; however, there was no statistical significance in the outcome between the two groups (p > 0.05). In 48 cases that received initial immunosuppressive treatment (glucocorticoid alone = 18, in combination with azathioprine = 20, or with mycophenolate mofetil = 10), 41 (85.4%) patients survived with a native liver, and there was no statistical difference in prognosis among the three types of immunosuppressive treatments. Serum albumin levels and decompensated cirrhosis at presentation were identified as independent factors influencing the likelihood of death or the need for liver transplantation (OR 0.814 [95% CI 0.670–0.989], p = 0.039; OR 0.146 [95% CI 0.022–0.963], p = 0.046).ConclusionThe majority of paediatric AIH patients survive with a native liver, and the outcome is not related to the type of immunosuppressive therapies but to decompensated cirrhosis at presentation.